2020
DOI: 10.3390/cryst10090797
|View full text |Cite
|
Sign up to set email alerts
|

Polycarboxylated Eggshell Membrane Scaffold as Template for Calcium Carbonate Mineralization

Abstract: Biomineralization is a process in which specialized cells secrete and deliver inorganic ions into confined spaces limited by organic matrices or scaffolds. Chicken eggshell is the fastest biomineralization system on earth, and therefore, it is a good experimental model for the study of biomineralization. Eggshell mineralization starts on specialized dispersed sites of the soft fibrillar eggshell membranes referred to as negatively charged keratan sulfate mammillae. However, the rest of the fibrillar eggshell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
5
0
2
Order By: Relevance
“…After treatment with sodium trimetaphosphate, phosphate groups were introduced onto the surface of type I collagen and strengthen the mineralization of ESM by forming calcium phosphate crystals [ 99 ]. In addition, it was shown that polycarboxylated ESM contained more surface nucleation sites for CaCO 3 mineralization [ 100 ].…”
Section: Application Of Eggshell Membrane As a Novel Biomaterialsmentioning
confidence: 99%
“…After treatment with sodium trimetaphosphate, phosphate groups were introduced onto the surface of type I collagen and strengthen the mineralization of ESM by forming calcium phosphate crystals [ 99 ]. In addition, it was shown that polycarboxylated ESM contained more surface nucleation sites for CaCO 3 mineralization [ 100 ].…”
Section: Application Of Eggshell Membrane As a Novel Biomaterialsmentioning
confidence: 99%
“…Besides that, ESM-BAP and ESM were both network structures composed of highly crosslinked protein fibers and cavities, while the microstructure of ESM-BAP was more compact compared with that of ESM (Figure 2b) (Li, Lan, et al, 2008). This was because that ESM fiber was wrapped up by BAP molecule and then results in the decrease of 1515 cm −1 , and 1350-1310 cm −1 were described to the existence of C=O, N-H, and C-N separately (Arias et al, 2020;D'Souza et al, 2013), illustrating that typical protein structure existed in the ESM, BAP, and ESM-BAP. After immobilized BAP on ESM with genipin, the new peak appeared at 1725 cm −1 , which was caused by the incomplete crosslinking of -COOCH 3 at genipin molecule C11 position (Gnanasambandam & Proctor, 2000).…”
Section: Comparisons Between Esm and Esm-bapmentioning
confidence: 97%
“…Komponen utama dari kulit telur adalah CaCO3 dimana terdapat sebanyak 94%-97% kadar kalsium karbonat dalam kulit 1 butir telur, yang setara dengan 1,5 gram kalsium. 13,22,23 Selain itu terdapat juga fosfor dan magnesium, dan sejumlah kecil natrium, kalium, seng, mangan, besi, dan tembaga. 15,24,25 Kulit telur dapat berasal dari bermacam hewan seperti ayam dan bebek.…”
Section: Gambaran Umum Dan Kandungan Kulit Telur (Gallus Domesticus)unclassified
“…Berdasarkan sebuah penelitian mengenai kadar kalsium tepung kulit telur unggas yang dilakukan perendaman dengan berbagai pelarut, penggunaan CH3COOH sebagai pelarut menghasilkan tepung kulit telur yang baik dibandingkan dengan pelarut lain. 17,23,26,27 Review Article…”
Section: Gambaran Umum Dan Kandungan Kulit Telur (Gallus Domesticus)unclassified